2006
DOI: 10.1007/s10495-006-7979-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of superoxide and dissipation of mitochondrial transmembrane potential by vitamin K2 trigger apoptosis in human ovarian cancer TYK-nu cells

Abstract: We reported previously that vitamin K(2) selectively induces apoptosis in human ovary cancer cells (TYK-nu cells) and pancreatic cancer cells (MIA PaCa-2 cells) through a mitochondrion-dependent pathway. In the present study, we examined the details of the mechanism of vitamin K(2)-induced apoptosis in TYK-nu cells. We found that superoxide (O(2)(*-)) was produced by TYK-nu cells between 2 and 3 days after the start of treatment with vitamin K(2), whereas it was produced within 30 min after the start of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…Because mitochondrial dysfunction is implicated in VK2-induced apoptosis (Shibayama-Imazu et al, 2006), we next examined the effect of VK2 on the mitochondrial-mediated apoptosis pathway. To examine the effect of VK2 on mitochondrial membrane potential, HL60 cells were treated with VK2 or the proton ionophore FCCP, and mitochondrial membrane potential was measured by flow cytometry using Rhodamine 123.…”
Section: Resultsmentioning
confidence: 99%
“…Because mitochondrial dysfunction is implicated in VK2-induced apoptosis (Shibayama-Imazu et al, 2006), we next examined the effect of VK2 on the mitochondrial-mediated apoptosis pathway. To examine the effect of VK2 on mitochondrial membrane potential, HL60 cells were treated with VK2 or the proton ionophore FCCP, and mitochondrial membrane potential was measured by flow cytometry using Rhodamine 123.…”
Section: Resultsmentioning
confidence: 99%
“…We did observe an increase in H 2 O 2 in fresh lysates from Ad-TERE1-infected J82 cells consistent with TERE1-mediated synthesis of vitamins K-2 or K-3. Both vitamin K-2 and K-3 are redox-cycling and alkylating quinones known to generate oxidative stress (superoxide and H 2 O 2 ), alkylate thiols and amines (O'Brien, 1991) and lead to different types of growth inhibition, autoschizis, necrosis, or apoptosis (Lamson and Plaza, 2003;Shibayama-Imazu et al, 2006;Jamison et al, 2010). This also suggests the possibility that TERE1 expression may be an oxidative stress liability that is selected against during tumor cell metabolic reprogramming to the invasive phenotype.…”
Section: Loss Of Tere1 Expression and Bladder Cancer Progressionmentioning
confidence: 99%
“…As a ligand for SXR, vitamin K-2 can activate LXR targets such as APOE and the ABC transporters that efflux vitamin K and cholesterol (Shukla et al, 2007;Chisaki et al, 2009). Pharmacological application of vitamins K-2 and K-3 are also linked to oxidative stress (Gilloteaux et al, 2006;Shibayama-Imazu et al, 2006;Shearer and Newman, 2008;Amalia et al, 2010). APOE is believed to play a role in oxysterol-induced efflux as part of a lipoprotein-mediated defense against oxidative stress (Laffitte et al, 2001;Landes et al, 2003;Carter, 2007;Rezen et al, 2010).…”
Section: Implications Of Tere1 Protein Interactions With Apoementioning
confidence: 99%
“…Previous studies have revealed that VK2 are involved not only in Á-carboxylation of proteins but also in the Á-carboxylation independent function, thus suggesting that VK2 possess both Á-carboxylation-dependent and -independent actions (26). As an example of the Á-carboxylationindependent action of VK2, vitamin Ks has been demonstrated to have an anti-proliferative effect in many types of cancer cells including HCC (14,15,18,20,24,(26)(27)(28)(29)(30). In addition to anti-proliferative effects, VK2 also suppresses the invasion of HCC cells (18).…”
Section: Discussionmentioning
confidence: 99%